2022
DOI: 10.3389/fcimb.2022.864912
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effect of Tacrolimus (FK506) or Everolimus and Azoles Against Scedosporium and Lomentospora Species In Vivo and In Vitro

Abstract: Scedosporium and Lomentospora infections in humans are generally chronic and stubborn. The use of azoles alone cannot usually inhibit the growth of these fungi. To further explore the combined effect of multiple drugs and potential mechanisms of action, we tested the antifungal effects of tacrolimus (FK506) and everolimus in combination with azoles in vitro and in vivo on 15 clinical strains of Scedosporium/Lomentospora species and detected the level of Rhodamine 6G, ROS activity, and apoptosis. The in vitro r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Our patient was on tacrolimus, which was previously shown to have synergistic effect with azoles in vitro and in a Galleria mellonella larvae model ( 14 ). However, this synergistic effect is obtained at high concentrations of tacrolimus (i.e., beyond the therapeutic range) and is counterbalanced by the strong immunosuppressive effect of this calcineurin inhibitor which may favor invasive fungal infections.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Our patient was on tacrolimus, which was previously shown to have synergistic effect with azoles in vitro and in a Galleria mellonella larvae model ( 14 ). However, this synergistic effect is obtained at high concentrations of tacrolimus (i.e., beyond the therapeutic range) and is counterbalanced by the strong immunosuppressive effect of this calcineurin inhibitor which may favor invasive fungal infections.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…In precious several studies, the EVL-induced cell survival rate in HaCat, Caki-1, and HepG2 cells were greater than 70% at 30 mM (≈28.75 mg/mL), especially up to 100 mM in HepG2 cells (Yamamoto et al, 2013;Navarro-Villarań et al, 2016). Recent studies have also demonstrated the activity of EVL against Aspergillus, Scedosporium, and Lomentospora species (Wang et al, 2022). However, there have not been any published studies assessing the effects of EVL against dematiaceous fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian laboratory‐based study of 30 L. prolificans isolates, the MIC 50 values for voriconazole, posaconazole and isavuconazole were 8, 16 and 16 mg/L respectively 11 . Synergistic effects have been noted in vitro when tacrolimus, minocycline or terbinafine are added to triazole antifungals 12–14 . Although many of these studies only included a small number of patients, olorofim yielded an MIC 90 value of 0.25 mg/L against 30 L. prolificans isolates 11 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Synergistic effects have been noted in vitro when tacrolimus, minocycline or terbinafine are added to triazole antifungals. [12][13][14] Although many of these studies only included a small number of patients, olorofim yielded an MIC 90 value of 0.25 mg/L against 30 L. prolificans isolates. 11 Fosmanogepix (APX001) also has demonstrated efficacy in vitro and in a mouse model.…”
Section: Discussionmentioning
confidence: 99%